Basics of Theory of Ecological Crisis Management - Stajić, Ljubomir (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Today, it is clear that environmental accidents and processes represent, not only potential but also real causes of crises on which states must be aware of. The formation of the ecological crisis is growing exponentially, along with their consequences. The problem with the environmental crisisis lies not in the fact that they exist, but how we treat them. Exploring the causes of the crisis requires an interdisciplinary approach. At the micro level, this approach focuses on the role of individuals. At the middle level of research, focus is on organizational factors and processes that may play important role in causing the crisis. Macro level of approach lists possible causes that seem to make the crisis more or less inevitable and unavoidable features of the modern world. The crisis is also characterized by negative effects (perturbations, deregulation, conflict, confused action, intense stress, which leads to reckless actions) and positive effects (mobilization, solidarity, cooperation, improved adaptation to the environment, experiential learning). Furthermore, ecological crisis represents an emergency situation whose beginning and duration are not predetermined. Anti-crisis measures have failed mainly because of the numerous factors influencing on one hand, on a complexity of the crisis and, on the other hand, because of its continuously changing factors throughout the duration of the crisis. Managing ecological crisis occurs, therefore, as a permanently professional inventive and complicated process which aims to prevent the escalation of the crisis, as well as the elimination of the expected and actual negative consequences of the crisis. Mismanagement of such crisis drains system resources, interferes with its function and organization, impacts on the financial opportunities while achieving positive goals. Extreme mismanagement can lead to the entropy of the system itself. The purpose of this paper is to elaborate basic facts of managing crises process due to environmental accidents in order to either prevent or reduce the consequences they carry with them.